2014
DOI: 10.1111/1567-1364.12169
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of yeast mutants lacking alkaline ceramidasesYPC1andYDC1

Abstract: Humans and yeast possess alkaline ceramidases located in the early secretory pathway. Single deletions of the highly homologous yeast alkaline ceramidases YPC1 and YDC1 have very little genetic interactions or phenotypes. Here, we performed chemical-genetic screens to find deletions/conditions that would alter the growth of ypc1∆ydc1∆ double mutants. These screens were essentially negative, demonstrating that ceramidase activity is not required for cell growth even under genetic stresses. A previously reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…The experiments showed that the sphingolipid biosynthetic pathway is conserved in C. grubii (H99) and C. gattii (R265 and R272) strains. This is similar to the pathway that has been proposed in other fungi, such as C. albicans, A. fumigatus, and A. nidulans (34,37,(48)(49)(50)(51)(52)(53)(54). Sphingolipid biosynthesis can be divided into two parts with a common precursor, dhSph (d18:0).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The experiments showed that the sphingolipid biosynthetic pathway is conserved in C. grubii (H99) and C. gattii (R265 and R272) strains. This is similar to the pathway that has been proposed in other fungi, such as C. albicans, A. fumigatus, and A. nidulans (34,37,(48)(49)(50)(51)(52)(53)(54). Sphingolipid biosynthesis can be divided into two parts with a common precursor, dhSph (d18:0).…”
Section: Discussionsupporting
confidence: 72%
“…Pathways of sphingolipid biosynthesis and genes involved therein are well-characterized in several fungi, such as S. cereviseae, Aspergillus fumigatus, Aspergillus nidulans, C. albicans, Pichia pastoris, and others (34,37,(47)(48)(49)(50)(51)(52)(53)(54). In one example of P. pastoris, the pathway of GlcCer biosynthesis very closely fits with the pathway present in Cryptococcus (19,21,54).…”
Section: Sphingolipid Profile Of C Grubii (H99) and C Gattii (R265 mentioning
confidence: 94%
See 1 more Smart Citation
“…In future work, we will test how quantitative changes should be weighted with respect to structural changes. We will estimate such weight measures from well understood model systems based on larger data sets that are now becoming available (Voynova et al, 2014;Tarasov et al, 2014). However, this study shows that the structural composition of a lipidome is sufficient to recognize the degree of genetic alteration and growth temperature dependence in yeast strains in an unsupervised manner.…”
Section: Discussionmentioning
confidence: 99%
“…Every 40 min the labeling media were replenished by adding 1 volume of 5-fold-concentrated SC medium (buffered as described above) to 4 volumes of culture. Labeling was terminated after 2 h, and lipids were extracted as recently described (24) and desalted using butanol-water partitioning or Folch partitioning; the latter does not completely retain M(IP) 2 C in the organic phase. Lipids were deacylated using NaOH as described previously (25).…”
Section: Methodsmentioning
confidence: 99%